2022
DOI: 10.3389/fonc.2022.955979
|View full text |Cite
|
Sign up to set email alerts
|

The IFN-γ-related long non-coding RNA signature predicts prognosis and indicates immune microenvironment infiltration in uterine corpus endometrial carcinoma

Abstract: BackgroundOne of the most common diseases that have a negative impact on women’s health is endometrial carcinoma (EC). Advanced endometrial cancer has a dismal prognosis and lacks solid prognostic indicators. IFN-γ is a key cytokine in the inflammatory response, and it has also been suggested that it has a role in the tumor microenvironment. The significance of IFN-γ-related genes and long non-coding RNAs in endometrial cancer, however, is unknown.MethodsThe Cancer Genome Atlas (TCGA) database was used to down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…AC006369.1, and CCR7 were aberrantly expressed in BRCA, and in relation to survival outcomes. Similarly, Gu et al identified AC006369.1 as an IFNG-relevant lncRNA that was connected with prognostic outcomes and the TME in uterine corpus endometrial carcinoma ( Gu et al, 2022 ). Many studies have proven the essential function of CCR7 in BRCA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AC006369.1, and CCR7 were aberrantly expressed in BRCA, and in relation to survival outcomes. Similarly, Gu et al identified AC006369.1 as an IFNG-relevant lncRNA that was connected with prognostic outcomes and the TME in uterine corpus endometrial carcinoma ( Gu et al, 2022 ). Many studies have proven the essential function of CCR7 in BRCA.…”
Section: Discussionmentioning
confidence: 96%
“…Interferon-γ (IFN-γ) encoded by IFNG gene is the only member of the type II interferon family, which is an essential cytokine generated from activated T cells, natural killer (NK), and NK T cells in the tumor microenvironment (TME) (Dörrie et al, 1999;Wu H. et al, 2022;Wei et al, 2022). Cell death can provide host defense and maintain homeostasis (Niu et al, 2021;Wang Z. et al, 2022). IFN-γ can prime diverse inflammatory cell death mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A differentially methylated region with three individually significant probes was identified in monocyte data near the long noncoding RNA LINC03062 , alternative name UNQ6494 , on chromosome 9. This transcript has been linked to immune infiltration in endometrial carcinoma 41 and survival in lung adenocarcinoma 42 , but potential roles in neuroinflammation are unknown. The region is located ~50 kb downstream of its closest coding gene, GADD45G , which has functions related to DNA damage response and cellular stress signaling 43 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, emerging evidence exhibited that the expression of lncRNA AL365203.2 may predict the prognosis of HCC by regulating immune cell differentiation and function. It has been reported that NRAV was an immune-related lncRNA in several tumor types, [ 47 , 48 ] suggesting a possible association between cuproptosis and immune microenvironment and may represent an oncogene that predicts prognosis. High expression of NRAV was observed in pancreatic ductal adenocarcinoma and myeloma.…”
Section: Discussionmentioning
confidence: 99%